(3GdLeGgQ aj eYQaI GdLhGgQs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdPi deG JhMO HGdCRd hGdCHO , hJaQO HGdOhGe LYd GdHbGA ai GdOfjG YdI GdafGA , hGdSdGeI hGdUMI s
(3BNQgG (B:s
(3hai cJGH GdfNH abO HdZfG eG CQOfG hhajfG eG cfG hYOfG hCf fNJe GdcJGH HeKd eG EaJJMfG Hg ef GdMeO GdeaVd GdLGjO HGdNjQ Ydi LejY GdNdb GdeQZhH Edjg ai EfGdI GdCejQ GdSfO Gdedc GdeDjO GdSdWGf GdeYXe Je GdcJGH HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG eWGdYI deMeO Hf CMeO GdMfai GdYdGFi HGdbGgQIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B594s
Keywords: (3Gdadcs